Використання коефіцієнту стисливості газу при комп’ютерному моделюванні нестаціонарних режимів течії газу - Любченко, Д. С. (ХНУРЕ, 2023)
This work is devoted the issue of the impact of choosing an approximation formula for the gas compressibility factor on the distribution of gas flow parameters: mass consumption, pressure and temperature in the non-stationary regime of gas flow along a pipeline has been considered. The obtained results can be applied to calculate the transient regimes of gas flow during emergency and abnormal situations.
Keywords: коефіцієнт стисливості газу; нестаціонарні режими течії газу; ділянка трубопроводу; нештатні ситуації в газотранспортній системі